The Analysis of Corporate Strategy of PT SIG In Globalization Era - Gito, Aditya; Zikri Soleha, Fazah; Akbar, Moh Abrori; Zahirah, Nabila Ghina; Syafitri, Sulistiani (Journal of Entrepreneurship and Financial Technology, 2023)
This paper analyzes the corporate strategy and globalization of PT Semen Indonesia (SIG), the largest cement company in Indonesia. This case study aims to understand how SIG develops its business, the strategies used in global expansion, as well as the structure, control, and corporate culture that support these globalization efforts. In addition, this paper also discusses SIG's corporate governance, ethics, social responsibility and sustainability practices. This research uses qualitative analysis with case studies as the main approach. Data was collected through literature review, company annual reports, and other secondary sources. The analysis shows that SIG has successfully implemented diversification and integration strategies, both horizontally and vertically, to strengthen its market position and increase profitability. The company has also expanded into the global market through acquisitions and strategic alliances, with a focus on the Southeast Asian market. In conducting its business, SIG upholds the values of good corporate governance, business ethics, social responsibility and sustainability. The company has received numerous awards for its commitment to these practices. This case study provides valuable insights for stakeholders in the cement industry and other multinational companies looking to expand their business globally.